Welfare indicators in cattle farming in the face of heat stress: a review in climate change scenarios - de Souza, Italo Messias Ferreira; Sousa, Carlos Eduardo Lima; Pinto, Vanessa Sousa; Vilela, Luís Gustavo Paixão; Souza, Alinne da Silva; Cunha, João Paulo de Sousa; Araújo, Cláudio Vieira de; Gomes, Marina de Nadai Bonin; Silva, Lílian Kátia Ximenes; Martorano, Lucietta Guerreiro; Neves, Kedson Alessandri Lobo; Camargo-Júnior, Raimundo Nonato Colares; et al. (Frontiers in Veterinary Science, 2026)
This work consists of a narrative review that addresses the differences between European cattle and Zebu cattle in their resilience to environmental challenges. It was developed based on scientific articles, theses, dissertations, and technical documents available in recognized databases such as Web of Science, ScienceDirect, Scopus, and PubMed, prioritizing recent studies from 2020 to 2025 that are relevant to the topic. The method used was a narrative review, in which publications addressing the physiological, behavioral, bioclimatic, and adaptive production parameters of each animal group were selected, allowing for a comparative analysis of their main characteristics. The results indicate that European cattle, although highly productive, are less adapted to heat, while zebu cattle stand out for their hardiness, resistance to high temperatures, and lower incidence of diseases. The conclusion is that analyzing these differences is essential to guide breed selection, genetic improvement strategies, and the adoption of more sustainable production systems, favoring greater livestock efficiency and resilience under diverse environmental conditions.